PEMBENTUKAN DAN PERKEMBANGAN ALAT TES DISC: SEBUAH LITERATURE REVIEW - Alifia Damara Nurochim; Allivia Ayu Wardani; Anatasya Rafelinda Putri (Flourishing Journal, 2022)
Abstract: Personality is something that is inherent in all humans, making individuals unique and different from each other. Through personality we can predict an individual's behaviour, be able to adjust interactions with other people, and be able to determine what kind of character a person has in daily life. A personality is often abstract and difficult to understand, let alone predict. Through the development of psychological practice, a personality can be studied and measured through assessment. Personality assessment is a test to measure an individual's personality traits. Tests can be in the form of written tests or administered through interviews to measure the relevant cognitive and emotional traits. One such test is the DISC personality assessment, founded by Dr. William Moulton Marston in 1928. The personality dimensions measured consist of the personality functions of Dominance (dominant trait), Influence (nature of influencing others), steadiness (stability) and compliance (critical nature). This research was conducted to add to the body of literature regarding personality assessments and personality theories in the field of psychology. The research method used is in the form of a literature review sourced from several relevant scientific articles. In its application, the DISC test is now widely used as an instrument in recruitment in the human resources sector, which allows the characteristics of employees to be known, so that employers are able to hire people who would have good interactions with each other and fit within the workplace. Keywords: DISC, Personality Assessment, Personality Test, Psychological Test, Employee Recruitment Test. Abstrak: Kepribadian adalah hal yang melekat pada diri manusia, menjadikan suatu individu unik dan berbeda dengan yang lain. Melalui kepribadian, kita bisa memprediksi perilaku seseorang tentang suatu hal, mampu menyesuaikan interaksi dengan orang lain, serta dapat menentukan karakter seperti apakah kita dalam menjalani kehidupan sehari-hari. Kepribadian seseorang seringkali bersifat abstrak dan sulit untuk dimengerti apalagi diprediksi. Seiring berkembangnya kajian ilmu psikologi, kepribadian seseorang dapat dipelajari, diketahui, dan diukur melalui sebuah asesmen kepribadian. Asesmen kepribadian adalah tes yang digunakan untuk mengukur aspek individu secara psikis. Tes ini dapat dilakukan secara tertulis, proyektif, atau wawancara teradministrasi untuk mengukur kemampuan kognitif dan emosional seseorang. Salah satu jenisnya adalah asesmen kepribadian DISC yang ditemukan oleh Dr. William Moulton Marston pada tahun 1928. Demensi kepribadian yang diukur terdiri dari fungsi kepribadian Dominant (sifat dominan/kuasa), Influence (sifat mempengaruhi orang lain), Steadiness (kestabilan), dan Compliance (sifat pemikir/kritis). Penelitian ini dilakukan untuk menambah studi literatur mengenai jenis-jenis asesmen kepribadian serta teori-teori kepribadian dalam bidang psikologi. Metode penelitian yang digunakan adalah berupa literature review yang bersumber dari beberapa artikel ilmiah yang relevan. Dalam penerapannya, tes DISC ini banyak digunakan sebagai salah satu instrumen dalam perekrutan di dunia kerja sehingga dapat diketahui karakteristik dari masing-masing karyawan agar dapat terjalin suatu interaksi yang baik dan menjadi pertimbangan untuk penempatan karyawan di dalam perusahaan Kata kunci: DISC, Asesmen Kepribadian, Tes Kepribadian, Tes Psikologi, Tes Rekruitmen Karyawan